The nature of Contemporary Terrorism: Selected Features and Statistical Data - Lech Chojnowski (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2016)
The paper presents selected features of contemporary terrorism. It emphasizes the role of a religious factor, which to a large extent determines the specificity of the contemporary wave of this phenomenon. Religion is used to justify the scale and brutality of methods and techniques of terrorist attacks, and also allows to acquire fighters ready to sacrifice their lives by carrying out suicide attacks. The paper also points to other features of modern terrorism: its mediality, internationalization, spread of suicide attacks, lack of terrorist self-limitation in the use of violence, disintegration, on one hand, and attempts to create quasi-state structures (ISIS), on the other, variants of terrorism described by the terms cyber-terrorism and super-terrorism. In the second part of the paper, selected statistical data on terrorist attacks, broken down by their various types that complement the picture of modern terrorism, are cited.